The Effect of Organic and Non-Organic Shampoo Waste Water on Growth, Development, Mineral Matter Content of Corn Plant - DUMAN, Boran; GÜNAL, Işıl; YAĞMUR, Bülent (ISPEC Journal of Agricultural Sciences, 2023)
In this study, it was aimed to reveal the positive or negative effects of these different types of shampoos by investigating the effectiveness of organic and non-organic shampoo waste water on the growth, development and mineral content of the corn plant. For this purpose, the corn plant was grown under controlled conditions with water containing organic and non-organic shampoos. The results were evaluated by analyzing the growth parameters of the plant some mineral substances in the corn plant and the soil where the plant grows. According to the results of the research, it was concluded that both organic and non-organic shampoo waste waters affect the growth and development of the plant negatively, and when the effects of shampoo types on the analyzed parameters are compared, the negative effects of organic shampoos are more than those of non-organic shampoos.